2017
DOI: 10.1152/ajplung.00353.2017
|View full text |Cite
|
Sign up to set email alerts
|

Versican is produced by Trif- and type I interferon-dependent signaling in macrophages and contributes to fine control of innate immunity in lungs

Abstract: Growing evidence suggests that versican is important in the innate immune response to lung infection. Our goal was to understand the regulation of macrophage-derived versican and the role it plays in innate immunity. We first defined the signaling events that regulate versican expression, using bone marrow-derived macrophages (BMDMs) from mice lacking specific Toll-like receptors (TLRs), TLR adaptor molecules, or the type I interferon receptor (IFNAR1). We show that LPS and polyinosinic-polycytidylic acid [pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(75 citation statements)
references
References 89 publications
1
72
0
1
Order By: Relevance
“…Rhamani et al first described the role of the canonical Wnt/β-catenin/T-cell factor (TCF) pathway in regulating versican expression in airway smooth muscle cells (57)(58)(59). Using polyinosinic-polycytidylic acid (poly I:C) and lipopolysaccharide (LPS) to activate TLR3 and TLR4, respectively, we showed that the signaling cascade that includes TLR3 or TLR4, the TLR adaptor molecule, Trif, type I interferons (IFNs), and the type I IFN receptor (IFNAR1), increases versican expression by mouse macrophages, which implicates versican as an IFN-stimulated gene (60). Versican synthesis is also controlled by several different miRNAs which are modulated during inflammation (61)(62)(63).…”
Section: Versicanmentioning
confidence: 99%
See 1 more Smart Citation
“…Rhamani et al first described the role of the canonical Wnt/β-catenin/T-cell factor (TCF) pathway in regulating versican expression in airway smooth muscle cells (57)(58)(59). Using polyinosinic-polycytidylic acid (poly I:C) and lipopolysaccharide (LPS) to activate TLR3 and TLR4, respectively, we showed that the signaling cascade that includes TLR3 or TLR4, the TLR adaptor molecule, Trif, type I interferons (IFNs), and the type I IFN receptor (IFNAR1), increases versican expression by mouse macrophages, which implicates versican as an IFN-stimulated gene (60). Versican synthesis is also controlled by several different miRNAs which are modulated during inflammation (61)(62)(63).…”
Section: Versicanmentioning
confidence: 99%
“…Versican is essential during development (76,77) and it is now becoming apparent that it is an important component of the tissue inflammation caused by infection and tissue injury (10). Versican accumulates as part of the early inflammatory response in a number of human diseases often associated with the invasion of leukocytes including those in the vascular system (10,40,(78)(79)(80)(81)(82)(83)(84), lung (5,6,60,77,(85)(86)(87)(88)(89), brain and spinal cord (53,(90)(91)(92), intestine (93)(94)(95)(96), heart (97), liver (63), skin (98,99), eye (100, 101), pancreatic islets (102), and many different forms of cancer [reviewed in (103)(104)(105)]. The accumulation of versican in these tissues is usually associated with other ECM components that bind versican, such as hyaluronan (106,107), link protein, TSG-6, IαI, and CD44 (95, 96, 108-111) (Figure 1).…”
Section: Versican: a Component Of The Inflammatory Responsementioning
confidence: 99%
“…136 The TLR agonists, LPS and poly(I:C), stimulate versican expression in both murine BMDMs and alveolar macrophages in vitro 25 and in murine alveolar macrophages, as well as in stromal cells, in vivo. 29,127 We explored the mechanism of regulation of versican expression in macrophages through in vitro studies. Engagement of TLR4 or TLR3, by LPS or poly(I:C), respectively, triggered a signaling cascade involving the Trif adapter molecule, type I IFNs and their receptor, IFNAR1, leading to increased versican production.…”
Section: Versican As a Regulator Of Pulmonary Innate Immunementioning
confidence: 99%
“…A recent study demonstrated that macrophages co-cultured with versican deficient mesothelioma cells acquired a more pro-inflammatory phenotype with increased phagocytic activity 62 . Versican is an ECM component that is upregulated in cancers [63][64][65] , and it has been suggested to have immunosuppressive functions 66,67 . Other studies have identified the ECM component hyaluronan as being capable of stimulating TAMs to acquire an immunosuppressive M2like phenotype 68,69 .…”
Section: Discussionmentioning
confidence: 99%